Memorandum of Understanding between Khulna University of Engineering & Technology (KUET) and Brac University (2011) - Brac University; Khulna University of Engineering & Technology (KUET) (Brac University and Khulna University of Engineering & Technology (KUET), 2019)
The agreement made between Khulna University of Engineering & Technology (KUET) and Brac university for implementation of an Integrated Library System (lLS) using KOHA, Dspace and Vu Find at KUET Library.